5-Amino-6-methylquinolin-1-ium hydrogen malonate–malonic acid (2/1) - Ibrahim Abdul Razak; Suhana Arshad; Nuridayanti Che Khalib; Kaliyaperumal Thanigaimani (Acta Crystallographica Section E, 2013)
The asymmetric unit of the title compound, 2C10H11N2+·2C3H3O4−·C3H4O4, consists of one 5-amino-6-methylquinolin-1-ium cation, one hydrogen malonate (2-carboxyacetate) anion and one-half molecule of malonic acid which lies on a twofold rotation axis. The quinoline ring system is essentially planar, with a maximum deviation of 0.062 (2) Å for all non-H atoms. In the anion, an intramolecular O—H...O hydrogen bond generates an S(6) ring. In the crystal, the components are linked via N—H...O and O—H...O hydrogen bonds into layers parallel to the ac plane. The crystal structure also features weak C—H...O hydrogen bonds and a π–π stacking interaction with a centroid–centroid distance of 3.8189 (10) Å.